Term delivery following pyometra after in vitro fertilization and embryo transfer - Sathya Balasubramanyam; Thankam R Varma (Wolters Kluwer Medknow Publications, 2014)
A 30 year old woman presented 12 days after embryo transfer with lower abdominal pain and orange vaginal discharge. She was diagnosed to have pyometra. A conservative management with drainage of the pyometra was followed by an uneventful pregnancy and term delivery. Conservative management in a case of pregnancy with pyometra needs close supervision to ensure maternal and fetal well being.